Interpretation of myocardial injury subtypes in COVID-19 disease per fourth version of Universal Definition of Myocardial Infarction. (4th July 2021) - Salbach, Christian; Mueller-Hennessen, Matthias; Biener, Moritz; Stoyanov, Kiril; Preusch, Michael; Kihm, Lars; Merle, Uta; Schnitzler, Paul; Katus, Hugo A.; Giannitsis, Evangelos
Abstract: Background: Application of the 4th version of Universal Definition of Myocardial Infarction (UDMI) to characterize rates and prognostic relevance of myocardial injury in COVID-19 disease. Methods: This retrospective, single-centre observational study enrolled 104 patients hospitalized with SARS-CoV-2 infection. Kaplan–Meier analysis and multivariate Cox regression were used to identify influence of acute or chronic myocardial injury on a composite primary (mortality, incident acute respiratory distress syndrome, incident mechanical ventilation) and secondary endpoint (mortality, incident acute myocardial injury during hospitalization, incident venous thrombosis, pulmonary embolism or stroke). Results: A total of 27 (26.0%) patients presented with chronic myocardial injury, and 19 (18.3%) with acute myocardial injury. 42 patients(40.4%) developed an incident myocardial injury during hospitalization. The presence of acute or chronic myocardial injury on admission and incident myocardial injury during hospitalization were associated with higher rates of endpoints. Independent predictors for the primary endpoint were higher severity stages according to Siddiqi et al. classification system and history of dyslipidaemia. Maximal hs-cTnT and D-dimer concentrations during hospitalization showed an association ( r  = 0.61). Conclusions: Objective description of myocardial injury according to the 4th UDMI in the current COVID-19 pandemic is crucial in order to discriminate patients with acute myocardial infarction and acute, chronic or incident myocardial injury.